2016
DOI: 10.1194/jlr.m060574
|View full text |Cite
|
Sign up to set email alerts
|

CDP-diacylglycerol synthases regulate the growth of lipid droplets and adipocyte development

Abstract: Lipid droplets (LDs) are highly dynamic organelles that play a central role in mammalian energy storage. LDs are also involved in many cellular functions, including protein storage and degradation, and membrane and lipid trafficking (1-4). Each LD contains a hydrophobic neutral lipid core enclosed by a phospholipid monolayer (5). In mammals, the lipid core comprises mainly triacylglycerols (TAGs) and cholesteryl esters. The molecular events underlying the biogenesis of LDs remain to be determined (6). While se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 42 publications
5
45
0
Order By: Relevance
“…Phospholipids were extracted from microsomes isolated from yeast or mammalian cells, subjected to high performance liquid chromatography (HPLC) tandem mass spectrometry (MS/MS) and analyzed using Lipid Search software as described ( Qi et al, 2016 ; Fei et al, 2011c ).…”
Section: Methodsmentioning
confidence: 99%
“…Phospholipids were extracted from microsomes isolated from yeast or mammalian cells, subjected to high performance liquid chromatography (HPLC) tandem mass spectrometry (MS/MS) and analyzed using Lipid Search software as described ( Qi et al, 2016 ; Fei et al, 2011c ).…”
Section: Methodsmentioning
confidence: 99%
“…CDS1 is a key enzyme in this branching point where they convert PA into CDP-DAG for phosphatidylinositol (PI) and phsophatidylglycerol (PG) synthesis. Knocking down CDS1 increased the amount of PA, triggered the formation of giant lipid droplets and reduce the amount of PI and PG [37]. We observed that activation of VDR in human hepatocytes upregulated CDS1.…”
Section: Discussionmentioning
confidence: 66%
“…CDS has been linked with lipid metabolism [1,2,15,20,21], with a stronger effect on phosphatidic acid levels. CDS2 de ciency (while not CDS1) could impair the maturation of initial lipid droplets in cultured mammalian cells [21].…”
Section: ′-Utrs Are Major Players In Gene Regulation That Enable Locmentioning
confidence: 99%
“…CDP-diacylglycerol synthases (CDSs) are critical enzymes that catalyze the synthesis of cytidine diphosphate diacylglycerol (CDP-DAG) from phosphatidic acid to produce phospholipids such as phosphatidylinositol, phosphatidylglycerol, and cardiolipin [1,2]. The gene encoding CDS was rst cloned from Escherichia coli in 1985 [3], while the rst eukaryotic CDS was cloned from Drosophila in 1995, which shares 31% amino acid similarity with bacterial CDS [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation